Evidence-based practice profiles of nurses: a transcultural study† - Negarandeh Reza; Nazari Rajab; Kiwanuka Frank; Salisu Waliu Jawaula; Shayan Shah Jahan (Sciendo, 2022)
To compare (i) the evidence-based practice (EBP) profiles and (ii) socio-demographic characteristics of nurses in 4 selected low-middle income countries (LMICs).